1994
DOI: 10.1115/1.2928871
|View full text |Cite
|
Sign up to set email alerts
|

Forces and Moments Due to Combined Motion of Conical and Cylindrical Whirls for a Long Seal

Abstract: The mutual interaction effects of cylindrical and conical whirl on the dynamic fluid forces and moments, which act on a long annular seal, were studied experimentally. A whirling motion composed of cylindrical and conical whirls is actuated by intentionally giving the phase difference between the seal exit and inlet whirling movements. This whirling motion is believed to generate during actual pump running. The experiment was conducted by changing the phase difference, at various rotor speeds and with a pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…2 Numerical geometric structure and computational fluid dynamics method 2.1 The numerical information of the annular seal Figure 1A depicts the seal used in the paper, which is based on Kanemori's experimental model (Kanemori and Iwatsubo, 1994). The geometric information and simulation information of the annular seal are shown in Table 1.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Numerical geometric structure and computational fluid dynamics method 2.1 The numerical information of the annular seal Figure 1A depicts the seal used in the paper, which is based on Kanemori's experimental model (Kanemori and Iwatsubo, 1994). The geometric information and simulation information of the annular seal are shown in Table 1.…”
Section: Parametersmentioning
confidence: 99%
“…Childs (1982) mentioned the dynamic coefficients due to shaft angular displacements are also crucial in annular seals having characteristics of large length-diameter (L/D) ratio, especially in submerged pumps. The moment coefficients due to shaft misalignment angles were obtained by Askharone and Hensel, (1991) through finite element (Kanemori and Iwatsubo, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the phase of the whirl acts either as a stabilising or destabilising force. Kanemori and Iwatsubo (1994a) extend their work to a linear stability analysis using the logarithmic decrement on a real submerged motor pump including hydrodynamic forces and torques when carrying out the stability analysis. The individual contributions of the whirl and concentric motion to the stability of the system is evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Mutual relationship between pressure force and displacement of rotor against casing is usually described by means of the so called "seal dynamic coeffcients" [1][2][3][4][5][6][7][8][12][13][14] which can be incorporated into whole model of turbine set during its designing process. Three kinds of the dynamic coefficients can be distinguished: stiffness, damping nad inertia ones.…”
Section: Pressure Forces -Linear Modelmentioning
confidence: 99%